The Adoption of The Law Against the Perpetrators of Pimps - Gallarang, Jabal Nur; Priscalia, Maria (Department of Law, Universitas Islam Negeri Alauddin Makassar, 2024)
This study aims to explore the settlement of prostitution cases focused on the role of pimps in the city of Makassar and the steps that have been and will be done by the police in preventing the practice. The results showed that Polrestabes Makassar has implemented a strategy in accordance with Perkapolri number 14 of 2012 on Investigation Management. This approach includes planning, organizing, and conducting investigations consisting of Investigation, forced effort, examination, case title, settlement of Case Files, submission of suspects and evidence, until the termination of the investigation. Meanwhile, efforts to prevent and eradicate human trafficking, especially in sexual exploitation are realized through preventive and repressive actions by the Makassar Polrestabes. This reflects the commitment of the police in dealing with prostitution cases comprehensively, from investigation to prevention